Histo-Morphology Study of the Respiratory Portion of Goat Lung (Capra Hircus) in Baghdad Province - Noor Yousif (مجلة الانبار للعلوم البيطرية, 2021)
The Histo-mrphology were directed on the pneumonic alveoli of 6 male goats. The respiratory portion is composed of typical cuboidal epithelial cells with Clara cell, however, alveolar ducts are lined by simple squamous epithelium and alveoli were generally circular structures that opened into the alveolar conduits and alveolar sacs or respiratory bronchioles. Alveoli were made out of two kinds of cells for example Type-I pneumocytes and Type-II pneumocytes. Previous framed the mainlining epithelial cells of alveoli which were squamous in sort having noticeable perinuclear territory and central found the core, while the last were cuboidal fit as a fiddle with the midway found core and periodically found among the Sort I cells in the alveolar epithelium. The lung pulmonary parenchyma was enveloped by the mesothelium (squamous epithelium) layer of visceral pleura.